GURU PAI DAN KECERDASAN SPIRITUAL ANAK TUNAGRAHITA - Rahmayanti, Ismi (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2018)
Teacher's presence in the learning process has an important role, the teacher's role as a facilitator in the learning process, as a liaison and linking between the material to be taught to students. Students who have special need education, guidance and direction in carrying out life challenges, which are found in Islamic religious education such as children in general to increase their spiritual intelligence. One of the schools that implement the learning of Islamic Education is the YPLB Nusantara Depok. The role of the teacher in it is very influential in increasing the intelligence of children with needs especially one of them is children with intellectual disability YPLB Nusantara Depok has Islamic religious activities and learning that become habituations in daily life. The researcher raised the issue to describe how the role of Islamic Religious Education (PAI) teachers in improving the spiritual intelligence of mentally retarded children in YPLB Nusantara Depok. The approach used in writing is a qualitative approach, the type of research used is case study research. The results of this study can be concluded that the increased spiritual intelligence of mentally retarded children is the role of the teacher in improving the spiritual intelligence of mentally retarded children, namely as a facilitator and liaison between teachers and students, material delivery through lecture and demonstration methods. Through the material he teaches is religious material that is practiced in daily life, such as morality, prayer, ablution, recitation, memorizing the short letters of the Qur'an. So that the spiritual development of mentally retarded children emerges, in attitude, and behavior.